Transverse-sigmoid sinus dural arteriovenous fistula presenting with recurrent transient ischaemic attack: A technical case report. - Ramli Hamid, Marlina Tanty; Abdul Kadir, Khairul Azmi (Journal Of Cardiovascular, Neurovascular & Stroke, 2020)
Intracranial dural arteriovenous fistulae (DAVF) are uncommon and account for approximately 1% of all strokes. All transverse-sigmoid sinus DAVFs require treatment because of the low rate of spontaneous regression and frequent association with aggressive neurologic symptoms. Endovascular embolization which aims for permanent obliteration of the lesion is now the primary treatment modality for all DAVFs. We present a 56-year-old patient with long standing history of intermittent TIA-like symptoms. Magnetic resonance (MR) angiography revealed right transverse-sigmoid sinus DAVF and bilateral vertebral arteries occlusion. The patient’s symptoms completely resolved upon successful trans-arterial embolization of the DAVF.